Sweden : Financial Sector Assessment Program-Technical Note-Stress Testing. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note explains the stress testing approach of the 2016 Financial Sector Assessment Program in assessment of risk in the Swedish financial sector and provides the results of the tests. Stress tests covered three major segments of the domestic financial sector. The resilience of the Swedish banking system was tested against solvency, liquidity, and contagion risks. The solvency stress test suggests that banks would be resilient to severe economic distress. Bank liquidity stress tests suggest that banks could withstand severe funding and market liquidity shocks, but there are pockets of vulnerability. The overall stress testing exercise suggests that there is room for improvement in the individual components of authorities' stress testing framework.